Implementasi Keselamatan dan Kesehatan Kerja pada Aktivitas Karyawan Menggunakan Metode HIRARC - Santoso, Rachmat Budi; Kusnadi, Kusnadi; Nugraha, Asep Erik (Universitas Indraprasta PGRI Jakarta, 2025)
Occupational safety and health are important factors at this time for employees so that they can do their work productively. This is done to reduce the impact of the risk of work accidents on employees and the company. The problem faced by the company is that there are work accidents that occur in mixer machines and production room areas that have an impact on employee safety and health. The HIRARC method is used in this study as a tool to identify work accidents that occur, assess how much impact is caused by work accidents, and provide control to handle so that work accidents do not occur. The purpose of this study is to reduce the occurrence of work accidents in the company to achieve zero accidents. The results of the PT ABC study showed that the activities carried out had a fairly high risk so that they could cause disorders in the human body to cause death and could be prevented by actions such as adding air ventilation and tightening the use of PPE (Personal Protective Equipment).